PENGEMBANGAN MINUMAN PROBIOTIK KEKINIAN SEBAGAI PANGAN FUNGSIONAL DI KAMPUS UNIVERSITAS RIAU - Evy Rossi; Dewi Fortuna Ayu; Ayu Diana; Imelda Yunita; Erpiani Siregar; Yossie Kharisma Dewi; Jum’atri Yusri; Atika Zarefar (LPPM Universitas Andalas, 2025)
Indonesia's food and beverage industry continues to grow rapidly, especially for value-added products such as functional foods. Probiotic beverages, as a type of functional food, hold tremendous market potential. This activity is also expected to foster an entrepreneurial spirit among students through the development of innovative products that have high market potential. The method of implementing Campus Intellectual Product Business Development (UPIK) activities is carried out at the IbIKK entrepreneurship unit, Department of Agricultural Technology, Riau University. The activities were carried out from July to October 2024. The implementation of the programme was divided into six sequential main stages: (1) preparation and planning, including the initial product formulation design and the development of activity instruments; (2) a survey of market needs and preferences; (3) product formulation development and application; (4) intensive training and production demonstrations for the partners; (5) assistance in marketing strategies, packaging design, and product evaluation; and (6) final monitoring and evaluation. Partners (IbIKK Unit) produce and market functional foods in the form of Yoghurt, Kefir, and Kombucha in the form of contemporary drinks. The implementation team conducted monitoring and evaluation in the form of questionnaires to consumers (80 people) who were randomly selected. Based on this activity, it was concluded that the development of probiotic functional drinks at Riau University has great potential thanks to healthy lifestyle awareness and a broad market, but its success requires product innovation, campus support, and a mature strategy to overcome competition and limited resources.